Implications for technological reserve development in advancing age, cognitive impairment, and dementia. (10th August 2020) - Benge, Jared F.; Scullin, Michael K.
Abstract: This commentary draws connections between technological culture emergence and recent trends in using assistive technology to reduce the burden of Alzheimer's disease. By the technical-reasoning hypothesis, cognitively-impaired individuals will lack the cognitive ability to employ technologies. By the technological reserve hypothesis, social-motivational and cultural transmissibility factors can provide foundations for using technology as cognitive prosthetics even during neurodegenerative illnesses.